Mutations in type 3 reovirus that determine binding to sialic acid are contained in the fibrous tail domain of viral attachment protein sigma1. - Chappell, J D (1997)
The reovirus attachment protein, sigma1, determines numerous aspects of reovirus-induced disease, including viral virulence, pathways of spread, and tropism for certain types of cells in the central nervous system. The sigma1 protein projects from the virion surface and consists of two distinct morphologic domains, a virion-distal globular domain known as the head and an elongated fibrous domain, termed the tail, which is anchored into the virion capsid. To better understand structure-function relationships of sigma1 protein, we conducted experiments to identify sequences in sigma1 important for viral binding to sialic acid, a component of the receptor for type 3 reovirus. Three serotype 3 reovirus strains incapable of binding sialylated receptors were adapted to growth in murine erythroleukemia (MEL) cells, in which sialic acid is essential for reovirus infectivity. MEL-adapted (MA) mutant viruses isolated by serial passage in MEL cells acquired the capacity to bind sialic acid-containing receptors and demonstrated a dependence on sialic acid for infection of MEL cells. Analysis of reassortant viruses isolated from crosses of an MA mutant virus and a reovirus strain that does not bind sialic acid indicated that the sigma1 protein is solely responsible for efficient growth of MA mutant viruses in MEL cells. The deduced sigma1 amino acid sequences of the MA mutant viruses revealed that each strain contains a substitution within a short region of sequence in the sigma1 tail predicted to form beta-sheet. These studies identify specific sequences that determine the capacity of reovirus to bind sialylated receptors and suggest a location for a sialic acid-binding domain. Furthermore, the results support a model in which type 3 sigma1 protein contains discrete receptor binding domains, one in the head and another in the tail that binds sialic acid.